Study of the pollution by surfactants in a river of a high Andean micro basin - Choque Quispe, David (2020)
The surfactants linear alkylbenzene sulfonate (LAS), is used in large quantities in modern society, and wastewater containing it can contaminate groundwaters through runoff and sewers. The study aimed to determine the level of LAS in the Huatanay river; in Cusco city, Peru. Water samples were taken from nine points along the river, in the rainy and dry season in 2018. LAS surfactants were determined spectrometrically using methylene blue as indicator; dissolved oxygen (DO) and conductivity were also determined; both were correlated through Pearson coefficient at 5% significance, and analyzed in triplicate. The concentration of LAS in the dry season varied between 0.01 to 23.17 mg/L and in rains from 0.09 to 1.47 mg/L; the DO level shows values between 0.11 to 5.04 mg O2/L, and the conductivity varied from 777.7 to 2688.9 µS/cm. In conclusion, high levels of LAS considerably decrease the DO and increase the conductivity